Virtual home visits during COVID-19 pandemic: mothers' and home visitors' perspectives - Abdullah Al-Taiar; Michele A. Kekeh; Stephanie Ewers; Amy L. Prusinski; Kimberly J. Alombro; Nancy Welch (BMC, 2023)
Abstract Background The experiences of mothers enrolled in Maternal, Infant and Early Childhood Home Visiting (MIECHV) program with virtual home visiting (VHV) during the pandemic remain mostly unknown. This study aimed to describe in detail the experience of home visitors and mothers with VHV during COVID-19 pandemic. This is a prerequisite for guiding future efforts to optimize MIECHV services that are provided through virtual operation. Methods Focus groups discussion were conducted with home visitors (n = 13) and mothers (n = 30) who were enrolled in BabyCare program in Virginia from January 2019 to June 2022. This included mothers who received in-person home visiting (IPHV), VHV, or both (hybrid IPHV and VHV). Inductive analysis was used to identify emergent themes from the transcripts, then coding was conducted following a codebook that was developed by the research team. Results Both mothers and home visitors considered IPHV necessary for a proper assessment of developmental milestones of children, for the assessment of the growth of the child through measuring the weight and height/length of the child, for the mothers to open up and discuss sensitive issues like domestic violence, for building a relationship between home-visitor and the parents, and for other potential benefits (comprehensive assessment of the environment around the child inside and outside the house from home visitors' perspective and detecting abnormal health conditions in children from mothers' perspective). Both mothers and home visitors see that VHV has some role to play but not to be a replacement for IPHV. If VHV is to be used, video conference is preferred by both mothers and home visitors, as it allows for some assessment. Conclusion Mothers and nurses considered IPHV critical for proper and comprehensive assessment of the child and the family and also essential to build the nurse-client relationship. Both mothers and home visitors considered VHV supplementary to IPHV that can be used from time to time particularly with busy mothers. VHV may have little room with parents with intellectual disabilities and the difficulty in dealing with technology seems to be no longer a major issue.